Alternative splicing of KLF4 in myeloid cells: implications for cellular plasticity and trained immunity in cancer and inflammatory disease - Rosewell Shaw, Amanda; Bennett, Attoria; Fan, Daping; Ai, Walden (Frontiers in Immunology, 2025)
The role of transcription factor Krüppel-like factor 4 (KLF4) in the modulation of myeloid cells is well known. KLF4 is involved in the differentiation and polarization of monocytes and macrophages as part of the immune response after infection, in wound healing, and in cancer. In addition, KLF4 is essential in stem cell reprogramming and the phenomenon of trained immunity – a form of innate immune memory marked by epigenetic and metabolic reprogramming. A novel and underexplored dimension of KLF4 biology lies in its alternative splicing (AS), which generates distinct isoforms that may drive the transcription factor’s functions, depending on specific cellular environments, disease states, or signaling programs. This review presents current knowledge of KLF4 splicing in myeloid cells and explores novel connections for how KLF4 isoform diversity may contribute to cellular plasticity and differential immune responses of myeloid cells across physiological and pathological conditions.